Indeks Massa Tubuh dengan Keseimbangan Statis Pengguna Transtibial Prosthesis - Nur Rachmat; Muhammad Syaifudin; Hanifah Hanifah (Politeknik Kesehatan Tanjung Karang, 2017)
The balance of a person's body is affected by the Body Mass Index. Body Mass Index is the easiest way to estimate obesity as well as to be highly correlated with body fat mass, but it is also important to identify obese patients who have a risk of medical complications. Purpose of this study was to know correlation body mass index with the static balance of transtibial prosthesis user. The study was a quantitative research with a cross-sectional design. Location research in BBRSBD Prof. Dr. Soeharso Surakarta with sample were patients with post-amputation of transtibial as many as 15 people. Analysis of data was used correlation Pearson test. There was a correlation between body mass index with the static balance of transtibial prosthesis user, the coefficient correlation of -0.646 with significant and levels of correlation moderate. The value of normal body mass index has the highest static balance than lean body mass index and fat. Mass Index of the skinny body has a moderate static balance. Obese body mass index has the lowest static balance of body mass index thin and normal.